Mechanisms of thermal strengthening and deterioration in sandstone: Insights from characteristic stress and micro-crack analysis - Lizhi Yang; Junjie Li; Daoxue Yang; Wen Chen; Mengjian Wang (PLoS ONE, 2026)
With the global push towards energy transition, understanding the mechanical behavior of rocks under high-temperature conditions is becoming increasingly significant, such as nuclear waste disposal. Previous studies have demonstrated that the high-temperature heating has a great impact on the physical and mechanical properties of sandstone, exhibiting both thermal strengthening and deterioration phenomena. However, research on the characteristic stress and microcrack evolution of sandstone under thermal strengthening and deterioration conditions remains limited. The objective of this study is to examine the characteristics of stress, microcrack evolution, and failure mechanisms in sandstone under a range of high temperatures. Sandstone samples were heated respectively to 200°C, 400°C, 600°C and 800°C. The deformation and failure processes were monitored using acoustic emission (AE) and digital image correlation (DIC) techniques. The evolution of characteristic stress and microcrack development under both thermal strengthening and deterioration conditions was analyzed. The results show that the crack closure stress and its threshold ratio are proportional to temperature. When sandstone exhibits strength deterioration, the crack initiation stress and its threshold ratio decrease with increasing temperature. Conversely, when strength enhancement is observed, the crack initiation stress increases, while the threshold ratio initially rises and then declines. Moreover, the effect of thermal treatment on axial deformation is more pronounced than on radial deformation, with the elastic constant and Poisson’s ratio gradually decreasing as temperature rises. Microcrack evolution was predominantly tensile across temperatures, but the macroscopic failure modes varied: monocline shear failure at 25°C, tensile failure at 200°C, 400°C, and 600°C, and a mixed shear-tensile failure at 800°C, where shear cracks became most prominent. This study enhances the understanding of sandstone’s mechanical behavior under high-temperature conditions and provides valuable insights for engineering applications involving thermal treatment.